Associated factors to cervical dentin hypersensitivity in adults: a transversal study - Polyana Matos Alcântara; Nayara Franciele Figueiredo Barroso; Adriana Maria Botelho; Dhelfeson Willya Douglas-; Patrícia Furtado Gonçalves; Olga Dumont Flecha (BMC, 2018)
Abstract Background This cross-sectional study aimed to identify the factors associated to the cervical dentin hypersensitivity (DH) in Brazilian adult population. Methods Three hundred and eighty patients (67.2% women and 32.8% men) were assessed by questionnaire and thermal test with ice. Participants marked in a visual analogue scale (VAS) the intensity of pain, and a calibrated examiner (ICC 0.990) measured the scores using a caliper. Pain scores above 0.5 mm were considered sensitive teeth. The DH associated factors were investigated by clinical examination. The association between variables was assessed by Spearman correlation and the Chi-square test. Logistic regression was used to determine the variables that predict DH (p < 0.05). Results The mean age of participants was 24.08 years. In this population, 8958 teeth were evaluated, of those 3037 (33.9%) were diagnosed sensitive. The most prevalent associated factors to DH were abnormal tooth positioning (9.0%), occlusal trauma (6.5%) and gingival recession (5.6%). The erosion predicted significantly the DH on both simple (OR 7.85, p < 0.001) and multiple(OR 4.36, p < 0.001) analysis. Conclusion The exposure of dentinal tubules by erosion is probably the major predictor of dentin hypersensitivity. The healthy tooth is able to protect against DH.